2022
DOI: 10.3390/agriculture12050721
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Theory and Practice of Grassland Eco-Compensation in China

Abstract: In order to curb the phenomenon of grassland degradation caused by human activity, China has begun the exploration of grassland eco-compensation, setting an example for the ecological protection of grasslands and sustainable use of resources around the world. At this stage, China has invested more than 170 billion yuan in grassland eco-compensation, benefiting 12 million farmer and herder households. The related research involves various perspectives, scopes, and methods, but lacks systematic reviewing. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…In addition, several studies suggest that economic, social and psychological features are related to satisfaction with the policy [26,27]. A study by Li et al (2022) on grassland ecological compensation programs found significant differences in herders' policy satisfaction influenced by factors such as household income, payment cognition, and the size of household-owned grasslands [13]. Another study by Shen et al (2022) on herders in Damao County, Inner Mongolia, showed that householders who were older and better educated, and who had lower incomes from livestock, larger grasslands and weaker social connections were more likely to participate in ecological compensation programs [28].…”
Section: Rural Households' Attitudes and Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies suggest that economic, social and psychological features are related to satisfaction with the policy [26,27]. A study by Li et al (2022) on grassland ecological compensation programs found significant differences in herders' policy satisfaction influenced by factors such as household income, payment cognition, and the size of household-owned grasslands [13]. Another study by Shen et al (2022) on herders in Damao County, Inner Mongolia, showed that householders who were older and better educated, and who had lower incomes from livestock, larger grasslands and weaker social connections were more likely to participate in ecological compensation programs [28].…”
Section: Rural Households' Attitudes and Influencing Factorsmentioning
confidence: 99%
“…Positive results were achieved after the implementation of ecological compensation policies: the livelihood of rural households improved [10], the area of wetlands expanded, and the ecosystem functions of wetlands were restored [11,12]. However, wetland shrinkage and ecological degradation are still common in China, and it is necessary to build upon the pilot experiences and improve the wetland ecological compensation policies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Green foods are agricultural products with China Green Food certification. Generally, such green foods mainly come from ecological systems; the ecological raising systems allow the proper application of modern science and technology within the scope of ecological and economic principles [ 8 ]. Ecological pig-raising systems (EPRSs) use some unique methods to gain better environmental performance.…”
Section: Introductionmentioning
confidence: 99%
“…By examining the impact of the implementation of the Converting Food Crops to Forage Crops Policy (CFFP) in the pilot counties of Hebei Province from 2010 to 2020 on the development of the herbivorous livestock industry, Zhang et al [9] clarified that the CFFP can produce high-quality feed, improve the productivity of animal husbandry, and promote the sustainable development of agriculture and animal husbandry. Moreover, Li et al [10] systematically reviewed the relevant theoretical and practical research of grassland ecocompensation in China, summarized the five characteristics and shortcomings of grassland ecological compensation, and point out that future work should focus on the response mechanism of herdsmen's families and the improvement of compensation measures.…”
Section: Policies Of Agricultural Sustainable Developmentmentioning
confidence: 99%